Implementation of the Ijarah Contract in Sugarcane Land Leasing from the Perspective of the Compilation of Sharia Economic Law: A Case Study of Karya Dadi Village, Bandar Sakti District, Central Lampung Regency: Implementasi Akad Ijaroh Dalam Sewa Menyewa Lahan Tebu Perspektif Kompilasi Hukum Ekonomi Syariah Study Kasus Desa Karya Dadi Kec. Bandar Sakti Kab. Lampung Tengah - abdul abdul; desi wahyuni (Program Studi Hukum Ekonomi Syari'ah, 2026)
This study aims to analyze the practice of ijaroh (lease) agreements on plantation land from the perspective of the Compilation of Sharia Economic Law (KHES). The study was conducted in Karya Dadi Village, Bandar Sakti District, Central Lampung Regency, focusing on the case of seizure of leased land by a bank because the land was used as collateral by the owner, even though the five-year lease period was still in effect. This study uses a descriptive qualitative approach with data collection techniques of observation, interviews, and documentation. The results show that the ijaroh agreement between the landowner and tenant was conducted without written documentation, thus having no legal force when conflict arose. The transfer of land to a third party (bank) without tenant consent contradicts the principles of adl (justice), gharar (certainty), and taradhin (mutual consent) in KHES. Inhibiting factors include low community understanding of sharia law and weak legal protection for tenants. Community perceptions of ijaroh agreements remain traditional and not yet based on comprehensive sharia law. This study affirms the importance of agreement documentation and muamalah legal education for communities so that ijaroh implementation proceeds fairly and in accordance with sharia.